(untitled) (Pedagogy of Higher and Secondary Education, 2007)
In the given article the organizing-pedagogical conditions of the formation of the dialogue interaction skills are considered. The author of the article emphasizes the urgency of studying the given problem, as the dialogue interaction skills definitely determine readiness of the students for the future pedagogical activity.